Generalized Ordinary Differential Equations : Not Absolutely Continuous Solutions. - Kurzweil, Jaroslav (World Scientific, 2012)
This book provides a systematic treatment of the Volterra integral equation by means of a modern integration theory which extends considerably the field of differential equations. It contains many new concepts and results in the framework of a unifying theory. In particular, this new approach is suitable in situations where fast oscillations occur.
Keywords: Differential equations.; Integral equations.; Équations différentielles.; Équations intégrales.; MATHEMATICS -- Differential Equations -- Ordinary.; Differential equations; Integral equations